The Effect of Project-Based Learning (PjBL) on Students’ Learning Activities and Learning Outcomes in the Excretory System Topic at SMA Negeri 15 Medan - Adriana Yulinda Dumaria Lbn.Gaol; Newche Rolima Samosir (UNIVERSITAS PGRI MADIUN, 2026)
This study aims to analyze the effect of the Project Based Learning (PjBL) model on students’ learning activities and learning outcomes in the Excretory System topic. The study was motivated by the low level of student engagement and learning outcomes associated with teacher-centered instruction, which limits conceptual understanding. A quantitative approach with a quasi-experimental Control Group Design was employed. The sample consisted of an experimental class receiving PjBL instruction and a control class receiving conventional instruction. Data were collected through classroom observations and pretest–posttest assessments. Statistical analyses included the Shapiro–Wilk normality test, Levene’s Test for homogeneity, and Independent Samples t-Test at a 0.05 significance level. The normality test indicated that activity data were normally distributed in the control class (Sig. = 0.329) and experimental class (Sig. = 0.097). Homogeneity testing confirmed equal variances for learning activities (Sig. = 0.623) and learning outcomes (Sig. = 0.506). Hypothesis testing revealed significant differences in learning activities (t = -2.811; Sig. = 0.006) and learning outcomes (t = -5.580; Sig. = 0.000). The experimental class achieved higher mean scores than the control class. These findings indicate that Project Based Learning positively influences student engagement and academic achievement